COMPARISON OF DOSES RECEIVED IN THE MANDIBULAR CONDYLE, COCHLEA, AND PAOTID GLAND IN NEUROAXIAL TREATMENT (Brazilian Journal of Radiation Sciences (BJRS), 2015)
Sensorineural hearing loss is a common side effect in patients who undergo radiotherapy for the treatment of cancer tumors in the head and neck. In fractioned doses of radiotherapy, in the majority of intracranial tumors, the cochlea is the most affected organ. In addition to the cochlea, the mandible and the parotid glands are also exposed to radiation, which commonly leads to Osteoradionecrosis of the mandible and Xerostomia. In the head and neck regions, this can be complicated by the semi-independence of the positioning in this region, as regards the rigid cranium, connected to the semi-rigid mandible, and successive levels of the upper cervical spine and thoracic spine, which can lead to uncertainty in rotation as well as in head-neck movements, both up and down and side to side. The present study performed an intercomparison of the doses applied through four radiotherapy planning techniques for the neuroaxial regions of the cochlea, mandible, and parotid glands, considering the changes carried out in each planning technique, including the protective shield, the angulations gantry and the field size. The results obtained by applying the half beam and angled field techniques varied in the cochlea by an average of 113.8% from the prescribed dose, whereas when applying the angled field technique with and without the mobile gap, the results varied in 104.5%. In the mandible, the half beam and angled field techniques showed that the dose varied an average of 16.5%, while in the techniques with and without the mobile gap, the variation showed an average of 116.4%. These values were also received by the parotid glands, which overlap the mandible. It can therefore be concluded that the protection shields of the first two techniques were less efficient in protecting the mandible due to its modeling.